2021
DOI: 10.1088/1755-1315/939/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the impact aimed at improving the efficiency of fiber cleaning

Abstract: Since cotton cleaning in Uzbekistan is carried out mainly manually, this paper discusses the methods and technologies established in the process of cleaning cotton and fiber. The process of fiber cleaning is one of the important processes that complete the technological process of cotton processing, given that the quality of fiber largely depends on the efficiency of this process, the research work on the mechanization of the type of collection and improving the efficiency of its cleaning is analyzed. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…It was found that the cleaning efficiency of the equipment increased from 58.8% to 62.5% due to the increase in fiber temperature from 25 0 C to 55 0 C in industrial grade II cotton, and the cleaning efficiency at 56 0 S was 62.0%. A similar situation is observed in the experiments conducted on IV-industrial grade cotton [24,25].…”
Section: Resultssupporting
confidence: 84%
“…It was found that the cleaning efficiency of the equipment increased from 58.8% to 62.5% due to the increase in fiber temperature from 25 0 C to 55 0 C in industrial grade II cotton, and the cleaning efficiency at 56 0 S was 62.0%. A similar situation is observed in the experiments conducted on IV-industrial grade cotton [24,25].…”
Section: Resultssupporting
confidence: 84%
“…As a result of the increase in the volume of machine-picked cotton in Uzbekistan, the fiber quality has been improved. The most important indicators of the produced fiber are the contents of contaminants and defective impurities [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers [7][8][9] have recommended the maximum number of cleaning repetitions in pile and sawdust drums to largely remove pollutants from cotton, and on this basis, the primary processing technology of cotton involves cleaning equipment. However, increasing the cleaning frequency by adding additional cleaning equipment could lead to an increase in defects in the produced fiber [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the speed of the air flow is further reduced, then after 18 m/s the particles of fibrous materials fall to the bottom of the pipe and move unevenly, bouncing. The results of monitoring the process of air transportation of fibrous materials showed that the raw materials are unevenly transferred to the pipes of pneumatic transport [5][6][7]. As a result, the cotton moves in separate sections in the pipe, somewhere concentrated, and somewhere in a rarefied state.…”
Section: Introductionmentioning
confidence: 99%